The effect of copper particles on dry sliding wear behavior of Fe-3mass%Cu - I., Agung; Syarif Junaidi S Djalil; Mariyam Jameelah, Ghazali (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.